Influencia de la calidad del servicio brindada por las trabajadoras sociales en la satisfacción de las gestantes atendidas en el policlinico el porvenir - essalud, distrito el porvenir, año 2015. - Iparraguirre Sanchez, Ana Melva (2015)
This research is descriptive, applied and was conducted with 123 pregnants taken care of in the area of work Social of the Policlinico El Porvenir-EsSalud, during the months of June - September of 2015, with the aim of knowing how it affects the quality of the service provided by the social workers in the satisfaction of the pregnants taken care of in the Policlinico El Porvenir - EsSalud. The research includes a systematic and detailed study of the aspects involved to assess the quality of service, satisfaction of users, as well as general aspects that characterize the study population, using the tools of observation, structured interview and a questionnaire for this. For the present study investigated further aspects that comprise the service quality and user satisfaction as the appearance of structure, comprising the quality of service in the Organization and use of media; the satisfaction of pregnant served according to trust, privacy and comfort, as well as the appearance of the process comprising the quality of service in friendly, timely information, interest in the needs of underserved pregnant; satisfaction at the good treatment, solution of the difficulties and limitations of personal, family, social and institutional, and finally the appearance of results including the quality of service on the effectiveness of counseling and guidance, quality of service on the health of the mother; satisfaction of pregnant served in understanding, reliability and friendliness of service, pregnant addressed towards safe motherhood psychosocial. In the present study, it is concluded that the quality of service offered by social workers in terms of structure, process and result has positively influenced the satisfaction of pregnant assisted at Policlinico El Porvenir, EsSalud, 2015.